İhaleye fesat karıştırma suçu - Sarı, Cahide Gülnur (My University, 2019)
Çalışmamızda tartışılan mesele, ihaleye fesat karıştırma suçunun hukuk tarihi içerisindekisüreci ve mevzuattaki düzenlemesidir. Bu itibarla ilk olarak ihale kavramı, ihalenin temelilkeleri, ihale mevzuatının tabi olduğu idareler, ihale süreci, ihale usulleri, ihaleye fesatkarıştırma suçunun Türk Hukuk sistemindeki tarihi gelişimi, mülga kanunlardakidüzenleniş biçimleri, suçun unsurları, suçun özel görünüş biçimleri, yaptırımları,kovuşturma usulü, görevli ve yetkili mahkeme ve doktrindeki eleştiriler ışığındamevzuattaki eksiklikler ele alınmıştır. İhaleye fesat karıştırma suçu, 765 Sayılı mülgaTürk Ceza Kanununda, dağınık ve farklı başlıklar ve maddeler altında düzenlenmişkenbu durumun uygulamada oluşturduğu sorunlar 5237 sayılı Türk Ceza Kanunu’nda tek birmadde suç tipini oluşturan hareketler sayılarak büyük ölçüde giderilmiştir.

The crimes about Bid Rigging in the legal history and their legislative arrangement hasbeen discussed in our work. The crime about bid rigging is a respectively recently issuedand embodied crime type. In this regard, firstly, the concept of tender, its ultimateprinciples, administrations that are subject to the bid rigging legislation, tenderingprocedure, tendering regulations, the historical process of the crime about Bid Rigging inTurkish Judicial System, the regulations in former laws, criminal provisions, appearanceof the crime, its sanctions, the method of prosecution, the competent and authorized courtand deficiencies in legislation in respect of the critics in doctrine are handled. The crimeabout public procurement has been issued under different and diverted titles and articlesin the former Turkish Penal Code No. 765. This situation caused several problems inexecution and these problems has been mostly eliminated with Turkish Penal Code No.5237 as the actions that constitute the crime have been listed in one article.
Keywords: collusive tendering; hileli davranış Bid rigging; Hukuk; İhale; İhaleye fesat karıştırma; Kamu hukuku; Law; Public law; tender